2017
DOI: 10.1021/acsomega.6b00436
|View full text |Cite
|
Sign up to set email alerts
|

Controlling T-Cell Activation with Synthetic Dendritic Cells Using the Multivalency Effect

Abstract: Artificial antigen-presenting cells (aAPCs) have recently gained a lot of attention. They efficiently activate T cells and serve as powerful replacements for dendritic cells in cancer immunotherapy. Focusing on a specific class of polymer-based aAPCs, so-called synthetic dendritic cells (sDCs), we have investigated the importance of multivalent binding on T-cell activation. Using antibody-functionalized sDCs, we have tested the influence of polymer length and antibody density. Increasing the multivalent charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
87
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 50 publications
(92 citation statements)
references
References 35 publications
2
87
0
1
Order By: Relevance
“…In comparison to free antibodies and monofunctional sDCs, the combination of anti‐CD3 and anti‐CD28‐decorated nanoworms: i) enhanced the formation of IS, ii) lowered the effective antibody concentration required for T cell activation, iii) prolonged T cell activation, iv) promoted specific T cell programming, and v) inhibited T regulatory cell activation. In 2017, the same groups investigated the effect of nanoworm length and antibody density on T cell activation . The authors showed that the increased multivalency of the antibody‐functionalized sDCs produced a significant reduction in the threshold of T cell activation.…”
Section: Nanoscale Materials For Immunotherapymentioning
confidence: 99%
“…In comparison to free antibodies and monofunctional sDCs, the combination of anti‐CD3 and anti‐CD28‐decorated nanoworms: i) enhanced the formation of IS, ii) lowered the effective antibody concentration required for T cell activation, iii) prolonged T cell activation, iv) promoted specific T cell programming, and v) inhibited T regulatory cell activation. In 2017, the same groups investigated the effect of nanoworm length and antibody density on T cell activation . The authors showed that the increased multivalency of the antibody‐functionalized sDCs produced a significant reduction in the threshold of T cell activation.…”
Section: Nanoscale Materials For Immunotherapymentioning
confidence: 99%
“…As with most multivalent cellular effectors, the T cell activation by sDCs occurred at much lower doses of antibody compared to activation by soluble monomeric ligand (Figure C). Interestingly, interferon release assays indicated that this enhancement was reflected in late stages of T cell activation as well and was sustained for an extended period of time—providing evidence that the multivalent effect goes beyond just an avidity increase …”
Section: Multivalency In Immune Cell Modulationmentioning
confidence: 97%
“…An important step in the activation of T cells via dendritic cell (DC) binding is the interaction of antigen‐loaded major histocompatibility complexes (pMHCs) of DCs with TCRs. Hammink et al . conjugated anti‐CD3 antibodies, which are known to trigger the TCR, to a semiflexible and linear polyisocyanopeptide scaffold (Figure A) resulting in synthetic dendritic cells (sDCs).…”
Section: Multivalency In Immune Cell Modulationmentioning
confidence: 99%
See 2 more Smart Citations